Quality Management of Islamic Education in Hasan Langgulung's Perspective - A. Nizar; Nurdyansyah Nurdyansyah; Akhtim Wahyuni (International Consortium of Education and Culture Research Studies, 2020)
This Study examines the lack of quality of Islamic education in a variety of education issues in general. Then this researcher will review how quality management of Islamic education in the perspective of Hasan Langgenger. The process of data collection is done by Naturally that the source of This research will be focused on the primary data that is the work of a Hasan Langgulung. Analysis results bring up the 3 themes discussed here: The quality of teacher education, the quality of Islamic education system, the role of parents on the quality of Islamic education. The study of the three themes is very useful to improve the quality management of Islamic education.